Impaction bone grafting has potential as an adjunct to the surgical stabilisation of osteoporotic tibial plateau fractures: Early results of a case series. Issue 6 (June 2015) - van de Pol, Gerrit J.; Iselin, Lukas D.; Callary, Stuart A.; Thewlis, Dominic; Jones, Claire F.; Atkins, Gerald J.; Solomon, Lucian B.
Abstract: Introduction: Osteoporotic tibial plateau fractures (TPFs) are difficult to treat with either open reduction internal fixation (ORIF) or acute total knee arthroplasty (TKA). They have high complication rates, poor outcomes and often fail in the short- to mid-term. We investigated the use of impaction bone grafting (IBG) as an adjunct to stabilise the fracture in a cohort of osteoporotic TPFs. Methods: Nine consecutive osteoporotic TPFs were surgically stabilised with ORIF augmented with IBG or with IBG alone (one pure depression fracture) using on average allograft from 2 femoral heads/case (range 1–4 heads or 25–100 cm 3 ). The median bone mineral density T -score of the patients was −2.9 (−2.5 to −4.5). All patients were mobilised weight-bearing as tolerated immediately after surgery and had regular follow-up to a minimum of 2 years where functional scores were taken and gait was assessed. Fracture reduction was assessed on plain radiographs and computed tomography (CT) scans; maintenance of fracture reduction was monitored using plain radiographs, CT and radiostereometric analysis (RSA). Bone graft remodelling was assessed by comparison of immediate post-operative CT scans with scans at a minimum of 1 year. Results: All surgeries were uneventful. All patients progressed to full weight bearing within 6 weeks of surgery and regained a normal gait by 3 months. Seven fractures healed with a cranio-caudal migration of less than 3 mm (range 0–2.6 mm using RSA and 0–2 mm using CT). Two fractures had an isolated posterolateral fragment depression of 13.5 mm and 9 mm, respectively, which did not affect the overall joint alignment or clinical outcomes at short-term follow-up. At latest CT follow-up, on average 51% of the graft area (range 36–70%) had remodelled into new host bone. Conclusion: Impaction bone grafting shows promising results as an adjunct to the surgical stabilisation of osteoporotic TPFs. In this case series the technique provided enough fracture stability for patients to mobilise weight-bearing as tolerated immediately after surgery and achieve full weight-bearing by the sixth postoperative week. There was no failure of fixation and 7 of the 9 cases healed with minimal fracture displacement.